Assessment of Hast Bahar (Flowering Season) for Yield and Quality of Pomegranate at Farmer’s Field - Singh, Pushpraj; Patel, V. K.; Desai, C. K. (International Journal of Bio-resource and Stress Management, 2024)
An on-farm trail (OFT) on assessment of flowering season of pomegranate was tested. The experiment was conducted with three treatments comprising mrig bahar flowering as a control and hast bahar flowering with and without application of micronutrients and kaolin clay during June to February for three consecutive years from 2019–2022 in the different farmer fields at the Tharad taluka of Banskantha district, Gujarat, India. The treatment T1 Mrig bahar (June-July) flowering recorded the maximum total number of flowers (293.67) hermaphrodite flowers (108.9) and fruit setting (71.85%). Further, T1 exhibited the highest average number of fruits plant-1 (79.0) and maximum fruit yield (11.78 kg plant-1) followed by T3 and T2 treatments (10.14 kg plant-1 and 9.02 kg plant-1) respectively. In terms of total fruit yield, Treatment T1 exhibited the highest fruit yield of (9813 kg ha-1). Whereas, maximum individual fruit weight 179.44 g plant-1 and Total Soluble Solids (15.75°Brix) were found in Treatment T3. Moreover, treatment T3 Hast Bahar (Sept–Oct) flowering with foliar spray of micromix 0.2% and kaolin Clay 4.0%) has the lowest average fruit cracking (6.30%) and the lowest incidence of sunburn (8.80%) across the three years. However, treatment T1 recorded highest average fruit cracking (18.90%). Further, during the Mrig bahar season, incidence of leaf spots and fruit rot was observed higher compared to the Hast bahar flowering. In case of economics, treatment T3 obtained the highest average income of 411813 ha-1 as compared to treatment T2 and T3 ` 353074 ha-1 and 333425 ha-1, respectively.